Sulfidation of nano zero-valent iron for enhanced hexavalent chromium removal performance - Xiu-juan Feng; Xiao-yi Wang; Dong-ming Li; Zhi-han Liu; Yue-long Yan (Water Science and Engineering, 2024)
Nano zero-valent iron (nZVI) and sulfidation-modified nZVI (S-nZVI) were synthesized and used to remove hexavalent chromium (Cr(VI)) in wastewater. Characterization of the products showed that the sulfidation process significantly changed the morphology of nZVI, with enhanced crystallinity. The effects of S/Fe ratio, pH value, and reaction temperature on Cr(VI) removal were studied. A S/Fe ratio of 0.5 was the most appropriate parameter, with a removal efficiency of 98% in the condition of pH = 2. The effects of anions (Cl−, NO3−, CO32−, and SO42−) and cations (Ca2+ and Mg2+) on the Cr(VI) removal efficiency were investigated, and the relevant mechanisms were discussed. The Cr(VI) removal efficiency of S-nZVI was significantly greater than that of nZVI, mainly owing to the existence of FeS layers that could protect Fe0 cores and prompt electron transfer. The aging and cycling experiments showed that S-nZVI could maintain its reactivity when facing the corrosion of water, and showed cycling stability. Thus, S-nZVI is an effective and feasible agent for the remediation of Cr(VI)-contained wastewater.